The Pancreatic Histological Changes of Morizella® Juice (Tanzania Medical Journal, 2020)
BackgroundMorizella juice is a nutritional supplement juice prepared from Moringa oleifera leaves and Hibiscus sabdariffa (HS) calyces. The juice is believed to have stabilizing effect on blood pressure (BP), anxiety, and to control glucose levels in some cases of diabetes. However, it is not recommended for consumption by infants and people with low blood pressure. Broad objectiveThe aim of the current study was to evaluate the pancreatic histological changes in rats fed with Morizella juice.Materials and MethodsA total of 18 healthy male and female Wistar rats, weighting between 183 and 224mg of 2-3 months old were used. The experiments were divided into short-term, mid-term and long-term test of six animals per group. Animals were sacrificed, the pancreatic tissues were harvested and histologically processed. Sections were examined and photographed using light microscope with in-built camera, and the number of Islet cells were measured in 40 high-power fields.ResultsMicroscopic investigation of the pancreatic tissue in both treated groups revealed morphological changes in hormone-secreting endocrine tissues as evidenced by putative proliferation of Islets of Langerhans when compared with the control group. The number of Islet cells was significantly higher (p < 0.05) in all treated groups at the dosages of 175 and 350 mg/kg body weight. It is important to note that our results also showed the increase in number of intra-islets capillaries in all treated rats.ConclusionsThe beneficial effect of Morizella juice was observed in rats in all doses studied herein. It was found to increase the number of pancreatic endocrine cells as evidenced by pancreatic tissue proliferation with significant increase in intra-islet vascularization.RecommendationsFurther research aiming at the evaluation of histological changes of Morizella juice by using special stains for detection of the proliferation of islet cells and to recognize the ?-cells of islets is recommended.Keywords: Morizella juice, Moringa oleifera, Proliferation, Hibiscus sabdariffa, Tanzania.